A comparison between the effects of drug costs and share of family income on drug costs in determining drug price. Issue 31 (6th August 2021) - Dong, Xiaobei; Tsang, Chi Chun Steve; Kotian, Anoop; Zeng, Jason; Tran, Michael; Wang, Junling
Abstract : Abstract: High health care and medication expenditures pose a financial burden on Americans seeking care. It is imperative to determine the role of affordability in influencing access to health care and medications. To investigate the association between financial burden and health care access by comparing the effects of absolute and relative financial burdens, measured by total health care/medication expenditure (Expenditure) and health care/medication expenditure as a share of annual family income (Expenditure Share), respectively. Delay in receiving health care services and delay in obtaining prescription medications. A cross-sectional analysis of the 2017 Medical Expenditure Panel Survey using multivariate logistic regressions with Expenditure and Expenditure Share variables standardized to facilitate comparison. While both absolute and relative financial burdens were found to be positively associated with the outcomes, the relative measure had a significantly higher association that was about twice as much as the absolute one. For the outcome of delay in getting health care, the standardized odds ratios (OR) for health care expenditure and health care expenditure as a share of family income were 1.13 (95% confidence interval [CI] = 1.09–1.18) and 1.25 (95% CI = 1.20–1.32), respectively. For the outcome of delay in getting medications, the standardized OR for medication expenditure and medication expenditure as a share of family income were 1.11 (95% CI = 1.08–1.15) and 1.23 (95% CI = 1.18–1.29), respectively. The study illustrated the importance of including income in policy considerations intended to balance value, access, and affordability. Specifically, income should be included in measures assessing the value of medications.